2010
DOI: 10.1080/01411594.2010.509614
|View full text |Cite
|
Sign up to set email alerts
|

Paranematic–nematic phase transition in liquid crystalline elastomers: a2H-NMR study

Abstract: In this study, selectively deuterium-labelled monodomain liquid single crystalline elastomers have been investigated by means of 2 H-NMR spectroscopy. The analysis of the spectral features as well as the study of the orientational properties in the paranematic and nematic phases confirmed the supercriticality of the paranematic-nematic transition as an intrinsic property of these systems. Moreover, the combined study of the spin-spin relaxation times (T 2 ) and the 2 H-NMR spectral linewidth measured in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…DNMR studies of selectively deuterated crosslinkers in side-chain LSCE monodomain films have recently confirmed the criticality of the PN-N phase transition being an intrinsic property of LSCE systems [325]. Some studies of deuterium T 1Z and T 2 relaxation time measurements have also been reported on LSCE samples [326,327]. Most DNMR studies of selectively deuterated LSCEs show broader spectra in samples containing deuterated crosslinkers [325,327] versus deuterated mesogens [326,328] or doped LSCEs [329].…”
Section: Polymeric Liquid Crystals and Lc Elastomersmentioning
confidence: 86%
See 1 more Smart Citation
“…DNMR studies of selectively deuterated crosslinkers in side-chain LSCE monodomain films have recently confirmed the criticality of the PN-N phase transition being an intrinsic property of LSCE systems [325]. Some studies of deuterium T 1Z and T 2 relaxation time measurements have also been reported on LSCE samples [326,327]. Most DNMR studies of selectively deuterated LSCEs show broader spectra in samples containing deuterated crosslinkers [325,327] versus deuterated mesogens [326,328] or doped LSCEs [329].…”
Section: Polymeric Liquid Crystals and Lc Elastomersmentioning
confidence: 86%
“…Some studies of deuterium T 1Z and T 2 relaxation time measurements have also been reported on LSCE samples [326,327]. Most DNMR studies of selectively deuterated LSCEs show broader spectra in samples containing deuterated crosslinkers [325,327] versus deuterated mesogens [326,328] or doped LSCEs [329]. Measurements and analyses of T 2 relaxation times in the I (PN) and N phases have been done on LSCE films containing deuterated crosslinkers.…”
Section: Polymeric Liquid Crystals and Lc Elastomersmentioning
confidence: 97%
“…These investigations successfully showed the fundamental role of crosslinker density in determining the thermodynamic features of the paranematic-nematic phase transition (PN-N) [80,81]. Recent 2 H NMR studies of side-chain LSCE monodomain films selectively deuterated on the crosslinker were published [213,214], confirming the criticality of the PN-N phase transition as an intrinsic property of LSCE monodomain systems. Since the particular two-step crosslinking reaction [213] is considered the "key-point" of the shape-memory properties of LSCEs, a detailed study was performed on several LSCE films 2 H-labeled on the crosslinker, as reported in Fig.…”
Section: Isotropic Phase Of Banana-shaped Lcsmentioning
confidence: 86%
“…In order to overcome these problems we present here a bilayered composite material in which the conductive surface layer is produced adding on the surface of a monodomain nematic LCE (based on a poly-siloxane backbone with chemical composition as in [6]) a thin conductive polymer layer. Coupling of the two layers was achieved by drop casting a waterborne solution of the conductive polymer poly(ethylenedioxythiophene):…”
Section: Introductionmentioning
confidence: 99%